Colorectal cancer liver metastatic growth depends on PAD4-driven citrullination of the extracellular matrix. Issue 1 (December 2018) - Yuzhalin, A.; Gordon-Weeks, A.; Tognoli, M.; Jones, K.; Markelc, B.; Konietzny, R.; Fischer, R.; Muth, A.; O'Neill, E.; Thompson, P.; Venables, P.; Kessler, B.; et al.
Abstract Citrullination of proteins, a post-translational conversion of arginine residues to citrulline, is recognized in rheumatoid arthritis, but largely undocumented in cancer. Here we show that citrullination of the extracellular matrix by cancer cell derived peptidylarginine deiminase 4 (PAD4) is essential for the growth of liver metastases from colorectal cancer (CRC). Using proteomics, we demonstrate that liver metastases exhibit higher levels of citrullination and PAD4 than unaffected liver, primary CRC or adjacent colonic mucosa. Functional significance for citrullination in metastatic growth is evident in murine models where inhibition of citrullination substantially reduces liver metastatic burden. Additionally, citrullination of a key matrix component collagen type I promotes greater adhesion and decreased migration of CRC cells along with increased expression of characteristic epithelial markers, suggesting a role for citrullination in promoting mesenchymal-to-epithelial transition and liver metastasis. Overall, our study reveals the potential for PAD4-dependant citrullination to drive the progression of CRC liver metastasis. Colorectal cancers (CRCs) often develop into untreatable metastatic disease of the liver. Here the authors report the modification of extracellular matrix proteins by citrullination in CRC metastases to the liver and propose that inhibition of citrullination could serve as therapeutic avenue in the treatment.